Strategies to optimize marker-assisted introgression of multiple unlinked QTL - Koudande, O.D.; Iraqi, F.A.; Thomson, P.C.; Teale, A.J.; Arendonk, Johan A.M. van (Springer, 2000)
To optimize designs to implement marker-assisted introgression programs aiming to introgress three unlinked quantitative trait loci (QTL), the present paper studies different alternatives versus a traditional backcross or intercross phase. Four alternative backcross strategies appear to be more advantageous by having 50 percent less genotyping load than a traditional backcross strategy tracking all three QTL at a time through a single line. A multiplication phase following the selection of homozygous animals at the three QTL as an intercross alternative allows doubling of the number of homozygous animals in a mouse model compared with the first intercross generation. Within the same model, a second intercross alternative with individuals carrying all three QTL at the first intercross results in a 12-fold increase in the number of homozygous, animals obtained in the first intercross generation. The same ranges of decrease are observed in the number of animals to be genotyped and the number of genotypings when targeting a fixed number of homozygous animals. An option with two lines each carrying two QTL through the backcross phase and coupled with the second intercross alternative appears to be the best introgression alternative. This option requires 76 percent fewer genotypings. 68 percent fewer animals to be genotyped and costs 75 percent less than an option in which all three QTL are introgressed through a single line.